Total mercury in rice plant Oryza sativa collected from Sekinchan, Selangor, Malaysia and associated health risks - Soong, Ai Cheng; Mohd Isa, Noorain; Aris, Ahmad Zaharin; Haris, Hazzeman; Looi, Ley Juen (Rynnye Lyan Resources, 2021)
Consumption of mercury-contaminated rice could pose a potential health risk to humans. In this study, total mercury (THg) concentrations in various parts (roots, stems, leaves, and grains) of rice plant (Oryza sativa) collected from Sekinchan, Selangor, Malaysia were analysed for risk assessment. The THg concentrations in collected samples were analysed by Direct Mercury Analyzer (DMA-80). The mean concentrations found in plant parts were as follows: root, 47.01±0.42 µg/kg; stem, 6.43±1.77 µg/kg; leaf, 26.25±4.71 µg/kg; grain, 2.64±0.42 µg/kg. THg distribution in rice plants was roots > leaves > stems and grains. The mean THg concentration in grain (2.64±0.42 µg/kg) was below the maximum permitted proportion stipulated by Malaysian Food Regulation 1985 (50.0 µg/ kg). The estimated weekly intake (EWI) of THg through rice was 0.07±0.01 µg/kg bw/ week for 60 kg adult, below the provisional tolerable weekly intakes (PTWI) as suggested by JECFA indicating unlikely to cause impairment of public health due to consumption of rice planted in this region. However, periodical monitoring of mercury pollution in Selangor area is crucial because mercury contamination in crops could jeopardize food safety and security.